The Palgrave Handbook of South-South Migration and Inequality - Crawley, Heaven; Teye, Joseph Kofi (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
"Across thirty three dazzling chapters, this groundbreaking collection from some of the world's leading migration scholars makes a major contribution to the field of migration studies. Centring south-south migration raises vital theoretical, methodological, and empirical questions for research on mobility globally which go far beyond geographical movements within the symbolic geography of the 'Global South'. Situated at the cutting edge of these debates, the contributors to this volume offer food for thought for scholars and students from a range of disciplines and locations." --Lucy Mayblin, Senior Lecturer, Department of Sociological Studies University of Sheffield. Author of Asylum After Empire: Postcolonial Legacies in the Politics of Asylum Seeking (2017) and Migration Studies and Colonialism (with Joe Turner, 2020) This open access handbook examines the phenomenon of South-South migration and its relationship to inequality in the Global South, where at least a third of all international migration takes place. Drawing on contributions from nearly 70 leading migration scholars, mainly from the Global South, the handbook challenges dominant conceptualisations of migration, offering new perspectives and insights that can inform theoretical and policy understandings and unlock migration's development potential. The handbook is divided into four parts, each highlighting often overlooked mobility patterns within and between regions of the Global South, as well as the inequalities faced by those who move. Key cross-cutting themes include gender, race, poverty and income inequality, migration decision making, intermediaries, remittances, technology, climate change, food security and migration governance. The handbook is an indispensable resource on South-South migration and inequality for academics, researchers, postgraduates and development practitioners. Heaven Crawley is Head of Equitable Development and Migration at United Nations University Centre for Policy Research (UNU-CPR), New York, USA, and Visiting Professor of International Migration at Coventry University's Centre for Trust, Peace and Social Relations (CTPSR), UK. She was previously Head of Asylum and Migration Research at the UK Home Office and Associate Director at the Institute for Public Policy Research, UK. Joseph Kofi Teye is Director of Research at the Office of Research Innovation and Development at the University of Ghana and Associate Professor of Migration and Development in the Department of Geography and Resource Development of the University of Ghana. He holds a PhD in Geography from the University of Leeds, UK.